PERAN ORANG TUA DALAM PENDIDIKAN AGAMA KRISTEN KELUARGA DI ERA DIGITAL: TANTANGAN DAN STRATEGI PEMBENTUKAN IMAN ANAK - Diani Jumentri Kabnani; Oriston Taneo; Debora Patolla; Mirma Liu; Jerti K. Talan (CV. ADIBA AISHA AMIRA, 2026)
Christian Religious Education (CHE) in the family context plays a crucial role as the foundation for the formation of children's faith, character, and spirituality. The family is the first space where Christian values ​​are introduced and lived out. However, the rapid advancement of digital technology presents new challenges for parents in carrying out their responsibilities as faith educators. This article aims to critically examine the role of parents in family Christian Religious Education in the digital era, while also identifying various challenges and relevant strategies for fostering children's faith. This research uses a qualitative approach through a literature review method, analyzing theological literature, Christian education, and scientific journal articles related to family CHE and the development of digital technology. The results of the study indicate that parents play a strategic role as role models of faith, spiritual guides, and wise supervisors of children's use of digital technology. Challenges faced include the influence of digital content that is inconsistent with Christian values, the decline in the quality of family relationships and interactions, and limited spiritual digital literacy among parents. Therefore, efforts are needed to strengthen contextual Christian religious education in families through the responsible use of technology, fostering family worship practices, and fostering sustainable communication of faith in daily life